Novel mechanistic study of HDAC6 regulation of rheumatoid arthritis via CMA: exploring potential therapeutic targets - Lin, Duoduo; Lai, Weipeng; Zheng, Ningning; Luo, Hongbin; Chen, Xiaole; Que, Wenzhong; Zhang, Nanwen (Frontiers in Pharmacology, 2024)
Rheumatoid arthritis (RA) is a systemic autoimmune disease. Its pathogenesis has not yet been clarified, so it is urgent to explore therapeutic targets. Here, we clarified the role of HDAC6 in the mechanism of action of RA through mediating chaperone-mediated autophagy (CMA) to provide a clinical treatment of RA.We used rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) and collagen-induced arthritis mice (CIA mice) as models of RA and pharmacological inhibitors as well as genetic interference with adeno-associated viruses to reduce the expression of HDAC6. We explored the influence of CAY10603 on RA-FLS proliferation and inflammation, as well as the expression of proteins related to the CMA signaling pathway. CIA model was constructed using DBA/1J mice. Arthritis symptoms in CIA mice were evaluated, and the expression and localization of CMA-related proteins in mouse ankle joints were examined.CAY10603 inhibited proliferation as well as the level of the molecular chaperone autophagy in RA-FLS. HDAC6 shRNA significantly reduced the clinical signs of arthritis in CIA mice, as did the expression of HDAC6 in the serum and ankle synovial tissues of CIA mice. Finally, it significantly inhibited the level of Hsc70 and LAMP-2A, which are involved in the CMA signaling pathway, in ankle joint tissues.Conclusion: Downregulation of HDAC6 may inhibit CMA and thereby ameliorate.